Islam and the Making of a Non-Violent and Peaceful Public Sphere in Indonesia - Maksimus Regus (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
This article attempts to elaborate on the position of Islam in creating a non-violent and peaceful public sphere in Indonesia. Through a critical review of previous studies and research on the issue, this article aims to answer the following main questions: How does Islam take a particular position in creating a peaceful public sphere in Indonesia? Second, what are the opportunities and challenges involved in making the sufficient role of constructing peaceful democracy and politics in Indonesia? Third, what lessons can be learned from Indonesia's position as the largest Muslim population in strengthening friendly public space? One of the focuses of this paper is to highlight the key role of Islamic civil society, which refers to Islamic organizations that significantly contribute to developing a peaceful public space in Indonesia.